Протеолитическая активность в кишечнике самок клеща Varroa jacobsoni - Барабанова, В.В. (Вестник зоологии, 1984)
Intestinal Proteolytic Activity in Varroa jacobsoni Females. Barabanova V. V.
Vestn. zool., 1984, No. I. Proteolytic activily in isolated intestines of Varroa jacobsoni
females has been determined in different periods of their life cycle. According to pH
optimum (3.5-4.0), benzoyl arginine amide destruction and localization (midgut) Varroa
proteases are found to be cathepsin-like. No proteolytic activity was found in Malpigh
tubules. Low level of fotal proteolytic activity is suggested to relate to high amino acid
content in bees’ haemolymph.